2013
DOI: 10.1007/s12257-013-0516-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved β-glucan yield using an Aureobasidium pullulans M-2 mutant strain in a 200-L pilot scale fermentor targeting industrial mass production

Abstract: -(1→3)-D-glucans with -(1→6)-glycosidic linked branches are known to be immune activation agents and are incorporated in anti-cancer drugs and health-promoting supplements. -Glucan concentration was 9.2 g/L in a 200-L pilot scale fermentor using mutant strain Aureobasidium pullulans M-2, which was from an imperfect fungal strain belonging to A. pullulans M-1. The culture broth of A. pullulans M-2 had a faint yellow color, whereas that of the wild-type had an intense dark green color caused by the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Other potential appications of A. pullulans include the production of several polysaccharides, such as β-(1 → 3)-d-glucans and pullulan (α-1,6 linked maltotriose), which are used as food additives, functional foods and raw materials for the medical, pharmaceutical and cosmetic industries (Moriya et al, 2013;Iyer et al, 2005;Kuan-Chen et al, 2010;Leathers, 2003). A. pullulans has also shown potential for phenol bioremediation of industrial effluents (dos Santos et al, 2009).…”
Section: Aureobasidium Sppmentioning
confidence: 99%
“…Other potential appications of A. pullulans include the production of several polysaccharides, such as β-(1 → 3)-d-glucans and pullulan (α-1,6 linked maltotriose), which are used as food additives, functional foods and raw materials for the medical, pharmaceutical and cosmetic industries (Moriya et al, 2013;Iyer et al, 2005;Kuan-Chen et al, 2010;Leathers, 2003). A. pullulans has also shown potential for phenol bioremediation of industrial effluents (dos Santos et al, 2009).…”
Section: Aureobasidium Sppmentioning
confidence: 99%
“…Previous report has demonstrated that both soluble and particulate β-glucans are able to bind to dectin-1, but dectin-1 mediated signaling pathway is not activated by soluble β-glucans [ 34 , 35 ]. Curdlan is a particulate β-glucan [ 35 , 36 ], whereas AP-PG is water soluble [ 8 , 9 ]. Futher, it has been reported that AP-PG does not exhibit binding activity to dectin-1 [ 37 ], while curdlan is known to be an agonist for dectin-1 and is recognized by dectin-1 [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Black yeast, Aureobasidium Pullulans produces a water soluble β-glucan (AP-PG) in growth medium under certain conditions [ 8 , 9 ]. AP-PG is characterized by being more highly branched with β-(1,6)-D-glycosidic linked glucose residues than β-glucans derived from other organisms [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black yeast, Aureobasidium pullulans is widely used in industrial production of pullulan by fermentation 9 . Further, A. pullulans extracellularly produces soluble β-glucan consisting of a β-(1,3)-linked glucose main chain and β-(1,6)-linked glucose branches under specific growth conditions 10 11 . The A. pullulans -cultured fluid containing the β-glucan as a main component exhibits immune stimulatory activity, and is consumed as a supplement in many countries, as well as A. pullulans -cultured fluid is believed to exhibit beneficial effects in delaying the onset a number of diseases, and has been reported to exhibit anti-tumor 12 13 , anti-allergy 14 , and also anti-infectious disease 15 16 17 activities in mouse models.…”
mentioning
confidence: 99%